An approach for heritage settlement classification using block patterns: The study of 37 typical colonial heritage settlements in the Americas - Wei Wei; Liyang Liu; Zhaosong Niu; Hongrui Li (Frontiers of Architectural Research)
Settlements serve as the tangible carriers of civilization, with historic urban blocks reflecting distinct cultural attributes that are essential for analyzing settlement types, exploring urban form characteristics, and refining spatial planning ideologies. Thus, this study focuses on the block as the fundamental morphological unit and introduces a structured research methodology from the typo-morphological perspective, comprising the following stages: Block Morphology Quantification, Block Pattern Types Extraction, Settlement Type Division, and Planning Ideology Discussion. This methodology can efficiently enhance the understanding of morphology and planning ideologies of heritage settlements by applying quantitative approaches to clustering settlements based solely on block pattern. For method validation, 37 typical colonial heritage settlements in the Americas is conducted as empirical study through the following process: first, quantifying block morphology; second, identifying block pattern types by K-means clustering; third, applying hierarchical clustering referring to the proportion of block pattern types within each case, resulting in the identification of four categories of “strategic core”, “corridor node”, “resource spot” and “overseas new town”; lastly, three key planning ideologies—“order”, “efficiency” and “practicality”—that shaped these settlements are derived from classification results accordingly. As empirical study result, the effectiveness of classifying heritage settlements using block patterns is validated.